التحليل الفسيولوجي لاختبار وينجات (Wingate) في القدرة والسعة اللاهوائية واهم المتغيرات الوظيفية خلال الاختبار وبعده للرياضيين - Hassan, Falah (Journal of Physical Education, 2016)
The aim of this study is to know what is the functional changes that connected with the maximum level to consuming of oxygen and power anaerobic and capacity anaerobic during doing the test Wingate for one time or twice in order to introduce scientific facts on these temporal responses. thus The sample of this research include players of AL-Qadisya team football 2014 – 2015 when numbers is (20) players after exclude. The goalkeepers and their average length is (180c) and their weight is (74kg). This performance had done by using bicycle of physical effort (Monark) model 894E and we have got results of maximum changes ability and capacity anaerobic, Then by using (fit mat pro) we have got (vo2max) changes and the heart rate. The whole test time is (30s) doing by the player on the bicycle after patting limitation of resistance according the body is weight (7.5%). Means each per/kg with (50 watt) in speeding turning (50 RPM/m). every players have been done this test for one time after that this test has been done twice separated by rest time for (45s) for each frequency. The researcher has got conclusion. One of the most important conclusion is the performance test Wingate for twice causes to increasing of maximum consuming oxygen , (EPOC), the heart rate and the number of breathing with comparing with its performance for one time. The drooping of oxygen disability with increasing the test frequency Wingate by compare with it performance for one time. The maximum ability productive was being done during the performance for one time with drooping the time of arrived to produce maximum ability by comparing of the performance which has been done twice.